Online Learning Experience in Nepal: An Observation during Covid-19 Pandemic - Chaudhary, Manoj Kumar; Chaudhary, Rajesh Kumar (International Research Journal of MMC, 2022)
An online learning has debatable issue since 1990s, though it entices the attention of entire globe throughout the pandemic covid-19. It this context, the considerable aim of this research work is to look over theprevalence of online learning in Nepal. Also, the paper inclined to know the experiences of Nepalese management graduates towards online learning vs physical classes and its effectiveness. This study has applied descriptive method for backing the purpose of this research. A purposive technique has been implanted to select the respondents. A survey based, the research instrument used consist of structured questionnaire. Dataprocessing with application of SPSS and MS excel for data analysis. This paper found that learning experience of both learning approach is determined by the way of takin and making an infrastructure for learning environment. Thus, it concludes that measuring the quality of these approach are largely depends on the operating capacity of individual and institutions as well in Nepalese climate as these approaches has their own strength and limitations. The educational stakeholders of Nepal have been experiencing dilemma of coping the challenges of new learning approach put forward by the covid-19. In this environment, this paper comprehends such issues and filled the gap in Nepalese context. Therefore, findings of this study would be important to all the academic players for their future survival strategies. Finally, there is big place available for further exploration for future researches as this paper has only considered the descriptive analysis.